Analysis of the Implementation of the Legalization of Customary Law Communities (MHA) in North Lombok Regency - Jemarut, Wihelmus; Dwi Ratna Kamala Sari Lukman; Ni Nyoman Ernita Ratnadewi; Ni Wayan Sridiani (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the implementation of Customary Law Communities (MHA) determination in North Lombok Regency (KLU), focusing on government actions, community responses, and encountered obstacles. This research employs an empirical legal research method. It was conducted from May to September 2024 through observation, interviews, and a literature review. Informants were selected using a purposive sampling technique. The study results show that determining MHA in KLU has only been completed at the Identification stage. The KLU MHA Identification Team identifies 13 (thirteen) Customary Law Communities (MHA): Bayan, Pansor, Salut, Wet Pengorong Amor-Amor, Wet Sesait, Kuripan, Pemaru Satan, Gubuk Bebekeq, Leong, Meleko, Orong Empak Pansan, Wet Sokong, and Jeliman Ireng. The thirteen aforementioned communities follow the criteria outlined in Article 6, Paragraph (6) of the North Lombok Regency Regional Regulation (PERDA KLU) No. 6 of 2020. The biggest obstacle in this process is the unavailability of technical guidance and the absence of definite work targets from the local government. The recommendation from the results of this study is that the KLU Regent who will be elected for the 2024-2029 period needs to include the MHA determination program in the KLU Regional Medium-Term Development Plan (RPJMD). Incorporating this program into the Regional Medium-Term Development Plan (RPJMD) document will ensure structured budgeting, develop technical guidelines, and measurable targets for effective implementation.